Preventative medicine and the dietetics of the soul in Galen’s moral treatises on the passions and errors of the soul - Molina González, Liliana Cecilia (Estudios de Filosofía, 2012)
The vast work of Galen of Pergamus -who was the physician to the Stoic Marcus Aurelius- includes various Treatises of a philosophical nature (especially those in which he analyses the causes of the passions and of the errors of the soul), whose main purpose is to understand human nature at large, and to put forward proper guides for its moral improvement. Galen split his exposition of the questions pertaining to the diagnosis and treatment of the passions and the errors of each one’s souls, since his main thesis - that the soul has a threefold structure (reason, intense emotions or passions, and desires)- requires this division. According to Galen, the treatment of the passions diverges from the treatment of cognitive disorders to which the errors of soul refer; which may be caused by immoderate passions or desires, and false opinions on goods and evils; which in the end mediate in the choice of a measured or, otherwise, immoderate life. The thread linking the Treatise on Passions and the Treatise on the Errors of the Soul is precisely that false opinions, which increase the violence exerted by our own passions whenever we have neither considered the causes (our beliefs and desires) of our excessive behavior, nor the value judgments with which we are used to judge daily circumstances of our daily life. The power of opinions lies precisely in increasing emotions’ quantum of force, making them immoderate and indomitable, or moderable.